Exercise and insulin resistance in PCOS: muscle insulin signalling and fibrosis. Issue 4 (April 2020) - Stepto, N K; Hiam, D; Gibson-Helm, M; Cassar, S; Harrison, C L; Hutchison, S K; Joham, A E; Canny, B J; Moreno-Asso, A; Strauss, B J; Hatzirodos, N; Rodgers, R J; et al.
Abstract : Objective: Mechanisms of insulin resistance in polycystic ovary syndrome (PCOS) remain ill defined, contributing to sub-optimal therapies. Recognising skeletal muscle plays a key role in glucose homeostasis we investigated early insulin signalling, its association with aberrant transforming growth factor β (TGFβ)-regulated tissue fibrosis. We also explored the impact of aerobic exercise on these molecular pathways. Methods: A secondary analysis from a cross-sectional study was undertaken in women with ( n  = 30) or without ( n  = 29) PCOS across lean and overweight BMIs. A subset of participants with ( n  = 8) or without ( n  = 8) PCOS who were overweight completed 12 weeks of aerobic exercise training. Muscle was sampled before and 30 min into a euglycaemic-hyperinsulinaemic clamp pre and post training. Results: We found reduced signalling in PCOS of mechanistic target of rapamycin (mTOR). Exercise training augmented but did not completely rescue this signalling defect in women with PCOS. Genes in the TGFβ signalling network were upregulated in skeletal muscle in the overweight women with PCOS but were unresponsive to exercise training except for genes encoding LOX, collagen 1 and 3. Conclusions: We provide new insights into defects in early insulin signalling, tissue fibrosis, and hyperandrogenism in PCOS-specific insulin resistance in lean and overweight women. PCOS-specific insulin signalling defects were isolated to mTOR, while gene expression implicated TGFβ ligand regulating a fibrosis in the PCOS-obesity synergy in insulin resistance and altered responses to exercise. Interestingly, there was little evidence for hyperandrogenism as a mechanism for insulin resistance.